2016
DOI: 10.1534/g3.116.033274
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling in Rat Inbred Strains and Experimental Cross Reveals Discrepant Genetic Architecture of Genome-Wide Gene Expression

Abstract: To test the impact of genetic heterogeneity on cis- and trans-mediated mechanisms of gene expression regulation, we profiled the transcriptome of adipose tissue in 20 inbred congenic strains derived from diabetic Goto–Kakizaki (GK) rats and Brown–Norway (BN) controls, which contain well-defined blocks (1–183 Mb) of genetic polymorphisms, and in 123 genetically heterogeneous rats of an (GK × BN)F2 offspring. Within each congenic we identified 73–1351 differentially expressed genes (DEGs), only 7.7% of which map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…In our cross between two yeast strains, we identified over one hundred hotspot regions, and found evidence for additional, weaker hotspots. Studies in many multicellular organisms, including plants ( Cubillos et al, 2012 ; Fu et al, 2009 ; West et al, 2007 ; Zhang et al, 2011 ), nematodes (Li et al, 2006; Rockman et al, 2010 ), mice ( Hasin-Brumshtein et al, 2016 ; Kelly et al, 2012 ; Orozco et al, 2012 ) and rats ( Heinig et al, 2010 ; Hubner et al, 2005 ; Kaisaki et al, 2016 ) have also observed trans -eQTL hotspots, showing that this phenomenon is not restricted to yeast. Compared to our yeast cross, human populations harbor orders of magnitudes more variants, and the human genome has many more genes and more extensive and complex regulatory regions that offer a large target space for regulatory variation.…”
Section: Discussionmentioning
confidence: 99%
“…In our cross between two yeast strains, we identified over one hundred hotspot regions, and found evidence for additional, weaker hotspots. Studies in many multicellular organisms, including plants ( Cubillos et al, 2012 ; Fu et al, 2009 ; West et al, 2007 ; Zhang et al, 2011 ), nematodes (Li et al, 2006; Rockman et al, 2010 ), mice ( Hasin-Brumshtein et al, 2016 ; Kelly et al, 2012 ; Orozco et al, 2012 ) and rats ( Heinig et al, 2010 ; Hubner et al, 2005 ; Kaisaki et al, 2016 ) have also observed trans -eQTL hotspots, showing that this phenomenon is not restricted to yeast. Compared to our yeast cross, human populations harbor orders of magnitudes more variants, and the human genome has many more genes and more extensive and complex regulatory regions that offer a large target space for regulatory variation.…”
Section: Discussionmentioning
confidence: 99%
“…Allelic heterogeneity, in which different mutations originated as a result of natural selection processes, genetic drift, or genetic migration at the same locus cause a similar phenotype, could be the phenomenon behind our results, as previously reported for other diseases (Chavez-Saldana et al, 2010). Moreover, the gene expression signature of specific phenotypes is influenced not only by the genotype but also by the architecture of the genome, epistasis and genome-ambient interactions (Kaisaki et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose intolerance and Type 2 diabetes in the GK rat have been extensively studied, and further studies revealed the GK strain also shows increased basal blood pressure compared to Wistar controls and salt sensitivity [63]. Several genetic loci have been identified that regulate not only the GK phenotypes but also its transcriptome and metabolome [64,65]. Furthermore, the specific genetic contributions evolve over the lifetime of the animal and the disease progression [66,67].…”
Section: Inbred Selection Models Of Metsmentioning
confidence: 99%